Personal Branding Ridwan Kamil Melalui Media Sosial Instagram Pasca Menjabat Sebagai Gubernur Jawa Barat - Qurotul Putri Riyadi; Raysa Nahtania; Hafsya Nur Abida; Tria Patrianti (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
Social media has a role in building relationships with each other, both through interaction and spreading information so that it can be known by many people. Indonesian political actors took advantage of this moment to build and create their self-image, one of whom was Ridwan Kamil or who is often called Kang Emil. He uses his Instagram social media @ridwankamil to build his image as a form of closeness to society. The image displayed by Ridwan Kamil is very diverse. The aim of this research is to find out Ridwan Kamil's personal branding on Instagram social media after he served as governor of West Java. The theory used in this research is the theory of the Eight Laws of Personal Branding by Peter F. Montoya. The method used is descriptive qualitative and data collection techniques by means of online observation on Instagram posts @ridwankamil and literature studies in the form of books, journals, theses, articles and websites related to this research. The results of this research are that the personal branding carried out by Ridwan Kamil in using Instagram social media is running according to his strategy, namely by uploading interesting photos or videos, and in the uploads there is a message that he wants to convey to his citizens which is packaged in a unique, different and funny way.